(untitled) (Texas Journal of Medical Science, 2025)
Respiratory diseases remain among the most common health problems in student populations. Frequent episodes of respiratory infections, influenza, bronchitis, and other airway diseases significantly affect students’ learning quality, cognitive performance, motivation, and psycho-emotional stability. The combination of intense academic workload and social stress further aggravates these effects.